Evaluating the efficacy of microbial antagonists in inducing resistance, promoting growth, and providing biological control against powdery mildew in wheat - Choudaker, Kariyappa R.; Singh, Vaibhav Kumar; Kashyap, Abhijeet Shankar; Patel, Aakash V.; Sameriya, Koshal K.; Yadav, Dhananjay; Manzar, Nazia; Kamil, Deeba; Prasad, Lakshman; Saharan, M. S. (Frontiers in Microbiology, 2024)
This study evaluates the biocontrol efficacy of three bacterial strains (Pseudomonas fluorescens DTPF-3, Bacillus amyloliquefaciens DTBA-11, and Bacillus subtilis DTBS-5) and two fungal strains (Trichoderma harzianum Pusa-5SD and Aspergillus niger An-27) antagonists, along with their combinations at varying doses (5.0, 7.5, and 10.0 g/kg of seeds), against wheat powdery mildew. The most effective dose (10 g/kg seeds) was further analyzed for its impact on induced resistance and plant growth promotion under greenhouse conditions. The study measured defense enzyme activities, biochemical changes, and post-infection plant growth metrics. All tested microbial antagonists at 10 g/kg significantly reduced PM severity, with B. subtilis strain DTBS-5 outperforming others in reducing PM severity and achieving the highest biocontrol efficacy. It was followed by B. amyloliquefaciens strain DTBA-11 and P. fluorescens strain DTPF-3, with the fungal antagonists showing no significant effect. Wheat crops treated with B. subtilis strain DTBS-5 exhibited substantial increases in defense-related enzyme activities and biochemicals, suggesting an induced resistance mechanism. The study found a 45% increase in peroxidase (POD) activity, a 50% increase in catalase (CAT) activity, a 30% increase in phenolic content, and a 25% increase in soluble protein content in the wheat plants treated with microbial antagonists. The study highlights the effectiveness of microbial antagonists, particularly B. subtilis strain DTBS-5, in managing wheat PM through biocontrol, induced resistance, and enhanced plant growth, offering a sustainable alternative to chemical treatments.